Whitefringed Beetles, Naupactus (= Graphognathus) spp. (Insecta: Coleoptera: Curculionidae) - Wayne N. Dixon (EDIS)
Naupactus leucoloma Boheman, the whitefringed beetle, was first collected in North America near Svea, Florida in 1936 (Buchanan 1939). This species and two others (N. minor (Buchanan) and N. peregrinus (Buchanan)) comprise the whitefringed beetle complex in North America (Buchanan 1947, Warner 1975). Whitefringed beetles are considered serious pests of many agricultural crops (Young et al. 1950) and have become pests of young pines planted on converted croplands in the South. This document is EENY-294 (originally published as DPI Entomology Circular 309), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2003.